2014
DOI: 10.3109/08916934.2014.939266
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response to and long-term effectiveness of anti-CD20 antibody in conventional therapy resistant Graves’ orbitopathy: A five-year follow-up study

Abstract: The aim of this investigations was to study the effectiveness of anti-CD20 antibody therapy in Graves' orbitopathy (GO) resistant to glucocorticoids. Five patients were entered in the study. The protocol required no improvement of orbital status after a recent course of glucocorticoids. Activity of GO was confirmed by three independent techniques: clinical activity score (CAS), (99m)Tc-labeled diethylene triamine pentaacetic acid ((99m)Tc DTPA) single photon emission computed tomography and magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, several case report studies demonstrated the relationship between rituximab administration and a decrease of inflammatory orbital infiltration, particularly complete depletion of CD20+ lymphocytes [11,14,17]. Significant changes of 99m Tclabelled diethylenetriaminepentaacetic acid orbital uptake and of T2 relaxation times of extraocular muscles on magnetic resonance imaging showing the effect of rituximab treatment for GO were also reported [18]. Positive correlations between CAS improvement and decrease of CD20+ and CD19+ lymphocytes and lack of a correlation between CAS improvement and TRAbs decrease in our study group favour the therapeutic effect of rituximab over the natural course of disease on GO clinical activity.…”
Section: Discussionmentioning
confidence: 97%
“…However, several case report studies demonstrated the relationship between rituximab administration and a decrease of inflammatory orbital infiltration, particularly complete depletion of CD20+ lymphocytes [11,14,17]. Significant changes of 99m Tclabelled diethylenetriaminepentaacetic acid orbital uptake and of T2 relaxation times of extraocular muscles on magnetic resonance imaging showing the effect of rituximab treatment for GO were also reported [18]. Positive correlations between CAS improvement and decrease of CD20+ and CD19+ lymphocytes and lack of a correlation between CAS improvement and TRAbs decrease in our study group favour the therapeutic effect of rituximab over the natural course of disease on GO clinical activity.…”
Section: Discussionmentioning
confidence: 97%
“…The implications of this data is that RTX may be indirectly responsible also for the depletion of autoreactive T cells, as a consequence of the decrease of T cell promoting cytokines and chemokines released by B cells, depleted by RTX. Preliminary studies have suggested that RTX can be effective either as first line treatment for moderate to severe GO or as additional therapy in patients resistant to ivMP [87][88][89][90][91][92][93].…”
Section: Targeting Cytokines/chemokines With Monoclonal Antibodiesmentioning
confidence: 99%
“…Other authors have described a decline of serum TSH receptor binding antibodies (TRAb) in patients with active GO after RTX therapy, whether the patients were on antithyroid drugs or euthyroid on L-T4 replacement therapy [12], suggesting again a direct effect of RTX on antibodies. Others have found that the beneficial effect of RTX on GO was not correlated to the decrease of serum TRAb [13]. A more precise picture of the effect of RTX on TRAb has been provided by the study of Vannucchi et al [14], who were not able to show a distinct decrease of circulating TSH receptor stimulating antibodies in patients with GD and GO after RTX, if compared to the decline of serum TSH receptor binding antibodies (TRAb) observed during the patients' follow-up when they reached the euthyroid state.…”
mentioning
confidence: 93%